Prevalence of liver cancer in Kazakhstan: a systematic review (Bangladesh Journal of Medical Science, 2024)
Background The study aimed to study the relative and absolute indicators of liver cancer (C22) in Kazakhstan over 10 years in the prism of a trend indicator (moving average), coefficient of variation (Cv), accounting reliability index (Idi).In 2022, in Kazakhstan, the incidence of liver cancer (C22) was 5.1 per 100 thousand people, mortality was 2.9, respectively, the index of reliability of accounting was 0.2.The unified risk of morbidity of the population of Kazakhstan with liver cancer for the period 2013-2022 amounted to 28.6%, mortality - 33.5%, respectively.Result Over the period 2013-2022, newly diagnosed liver cancer in Kazakhstan increased by 31%, the rate of decrease in the number of newly diagnosed liver cancers varied unevenly over the years, which demonstrates a high rate and amplitude of change from 105 to -140, which significantly complicates the prediction of this pathology.Conclusion: For the period 2013-2022, posthumously registered liver cancer consistently occupied the first place in the structure of specific gravity among all malignant neoplasms in Kazakhstan.  Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 643-654